Modelo conceitual de ciclone tropical na bacia do atlântico norte: estudo de caso - Santos, Anselmo Manoel dos (2018)
Tropical cyclones (CT's) are among the interference systems that play a key role on the planet. In this research, we present a comparative analysis of the cyclone cases (Hurricane Fred and Danielle) that occurred in the North Atlantic in September 2009 and August 2010. The pattern was presented at the same time as the cloud patterns at different stages of the tropical cyclone. It was also investigated as occurrences in the tropical poles, with a maximum temperature difference of 0.42μm and IR 10.8μm (WV-IR). CT was mapped, localized and expanded in deep convection centers. Soon after the Matlab scripts were created with the purpose of identifying OT's. The selection of the images was made using the McIDAS-V software, using the high-resolution data of the VFC, so that the channel was edited with greater amplitude of image and treated by a channel with a spatial resolution of 1Km. The results of the survey provided us with characteristics and patterns of clouds in the different phases of the tropical cyclone, as well as on the genetics involved for the formation of tropical cyclones. It can be verified whether the technology detection is being used, or if the DTB WV-IRW is an indicative indicator that at the moment, the same regions with the convention are severe, but noting the regions with possible surpluses of tops estimated by those who reveal relevant confidence.